Existence of W01,1Ω Solutions to Non-Coercivity Quasilinear Elliptic Problem - Jimao Xiawu; Shuibo Huang; Yingyuan Mi; Maoji Ri (Journal of Function Spaces)
In this paper we consider the existence of W01,1Ω solutions to following kind of problems −div∇up−2∇u/1+uθp−1=fx,x∈Ω;ux=0,x∈∂Ω where Ω is an open bounded subset of RNN>2, maxp−2N+1/p−1N−1,0<θ<1 and 1<p⩽1+N−1/N1−θ+θ, f is a function which belongs to a suitable integrable space.